The influence of freezing conditions on the organoleptic attributes of Iranian leafy vegetable foods - Koushki, Mohammad Reza; Mohammadi, Mehrdad; Haji Seyed Javadi, Nasrin; Komeily, Rozita; Moslemy, Masoumeh; Seyed Ahmadian, Fariba; Zali, Hakimeh (Archives of Advances in Biosciences, 2013)
The edible leafy vegetables contain nutritional ingredients that are necessary for human health and it is important that nutrients protection be monitored during processing and storage. The aim of this study was to study some organoleptic attributes of a very popular Iranian meal named Coco-Sabzi, which was prepared with a mixture of edible grinded leafy vegetable pre-stored at different frozen conditions. So, by sensorial evaluation we can conclude about nutritional loss of products. The mixture of five edible grinded leafy vegetables including Allium ampeloprasum var. porrum, Lepidium sativum, M. spicata (M. sativa), Ocimum basilicum and Allium porrum were stored at -9, -12 and -18oC for 120, 150 and 180 days. The organoleptic attribute of the prepared Coco-Sabzi was compared with the above three different time-temperature combinations during the frozen storage period. Results indicated that the best colors were observed at -18, -12 and -9oC, respectively. Taste and overall acceptability at -18oC after 120 and 150 days and also at -12oC after 180 days ranked 1st (P< 0.05). Data analysis showed that the color, taste and overall acceptability of samples were not statistically different at three different time-temperature combinations during the frozen storage period. As a result, organoleptic attribute during six months of frozen storage was affected by freezing temperature, not by frozen storage period